Pelatihan Perencanaan Keuangan Santri di Pondok Pesantren Bustanul Mansuriyah - Fahriyan Fariduddin; Edi Saputra; Aby Yazid Al Busthom; Hendri Hermawan Adinugraha (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
This financial planning training service program for students at the Bustanul Mansuriyah Islamic Boarding School aims to share knowledge and practical training in management knowledge in preparing monthly budgets and provide insight into the urgency of professional financial planning management to raise awareness of better personal financial management for students in Islamic boarding schools. Bustanul Mansuriyah Islamic Boarding School. The method applied to this service activity is the method of direct material decomposition as well as simulations and dialogues regarding management, financial management and intensive assistance in personal financial planning with a problem solving approach that has an impact on the welfare of students. The result of this community service is mentoring in proportional financial planning management and data obtained on average students have the ability to prepare personal financial planning well.